An investigation on the active control strategy for a high-speed pantograph using co-simulations. (April 2019) - Zdziebko, Paweł; Martowicz, Adam; Uhl, Tadeusz
The article presents simulation results on the active control strategy for a railway pantograph to improve contact quality in pantograph–catenary interface. Three different approaches were investigated: nominal torque tuning, torque active control and combination of them—combined control approach. The first control scenario minimizes the pantograph nominal uplift force exerted on the catenary. The second approach is based on active pantograph toque control, employing the proportional–integral–derivative controller, to compensate actual contact force error. The last control scenario links the above-mentioned approaches. Promising results are obtained employing the co-simulation environment recently presented by the authors.